The Role of Social Policy in Reducing Poverty in Three Canadian Provinces from 1999 to 2014 - Robinson, Jordan (Université d'Ottawa / University of Ottawa, 2018)
This correlational study uses quantitative data as well as qualitative document and policy analysis to consider the role that social policy has played in achieving poverty reduction in Canada’s provinces since 1999. Because social policy is only one among many factors influencing poverty and a social protection system consists of many programs, this research seeks to identify those factors, including social policies and/or social policy changes, which are most likely to have influenced poverty. This research finds that social policy and economic factors influenced poverty rates and trends over this period, albeit inconsistently across demographic groups and jurisdictions. The analysis suggests that it is very likely that social policy reduced poverty among families with children in Quebec and Ontario over this period. In contrast, social policy has become increasingly ineffective at reducing poverty among unattached adults in terms of both incidence (poverty rate) and depth (poverty gap). Finally, the evidence suggests that economic factors likely played an important role in reducing poverty in British Columbia and, to a lesser extent, in Quebec, but likely did not contribute to poverty reduction in Ontario. This research demonstrates the need for additional comparative research on how social policy and its evolution influence poverty rates at the provincial and demographic levels. To support such research (and evidence-based policymaking), this research also shows that there is a need for provincial and federal governments to collect and publish data on social programs and beneficiaries. Finally, the findings demonstrate the need for additional social programming aimed at preventing and relieving poverty among unattached adults who have seen very little improvement in their poverty risk over the past 15 years.
Keywords: poverty; social policy